Functional performance, anthropometric parameters and contribution to team success among Italian "Serie A" elite goalkeepers during season 2016-2017 - Longo, U. G.; Sofi, F.; Dinu, M.; Candela, V.; Salvatore, G.; Cimmino, M.; Jennings, J. M.; Denaro, V. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: Soccer is the world`s game, played by more than 120 million people. Different physical abilities, morphological and physiological characteristics are required for different playing positions. The purpose of this study is to describe anthropometric parameters and functional performances of goalkeepers, and these relationship with team success. METHODS: The study population consisted of 92 professional goalkeepers from the Italian soccer "Serie A" league. Anthropometric measurements and indicators of performance of matches were obtained from the Italian soccer league. Goalkeepers were divided into first-choice and substitutes. RESULTS: Goalkeepers who played at least one match were significantly older and heavier than those who did not play any game (P<0.0001). Minutes on the pitch, goals conceded, total saves and saves from both play sets and free kicks were significantly higher in the first-choice goalkeepers as compared to substitutes. However, by comparing first-choice with substitutes no significant differences for the ratio between goals against and saves by minutes played were observed. A significant positive correlation between points obtained by the team and ratio of goals conceded by minutes played (R=0.55; P<0.0001) as well as ranking position of the team achieved at the end of the season and the ratio of total saves by minutes played (R=0.51; P=0.001) was observed. A significant but inverse correlation between points obtained by the team and goal conceded was reported (R=-0.80; P<0.0001), as well as point obtained and ratio of total saves by minutes played (R=0.51; P=0.001). A lower ratio of goals conceded by minutes played was a significant predictor of total points achieved by the team (ß=0.712, SE=0.15; P<0.0001). Finally, a higher ratio of goal conceded by minutes played was also associated with a higher probability of success for the team at the end of the season. Goalkeepers who completed the season with a ratio of goal against by minutes played greater than 57.5 minutes had an increased probability of leading their team to the first 6 positions of the final ranking (OR=24.7, 95% CI: 2.1-297.3; P=0.01). CONCLUSIONS: Performance activities of the goalkeepers included in the rosters of the Italian soccer league significantly influenced the success of their team. A lower ratio of goals conceded by minutes played resulted to be the most significant predictor of overall team success. The present research extended previous research underlining the central role of goalkeeper for team success.